What is a 'Participatory Approach' and what makes it new in science and development? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Thomas Rosswall, CCAFS SC Chair. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya